Analisis Penerapan Pemasaran Online Terhadap Kelayakan Usaha Pada Usaha Hidroponik Di Kota Kendari (Studi Kasus Usaha Hidroponik Nuri Horti) - Imaraya, Orayeta; Bahari, Bahari; Dedu, La Ode Arfan (Innovative: Journal Of Social Science Research, 2024)
His study aims to determine the factors that influence the decision of rice farmers in adopting combine harvester technology innovations in Ngkaring-Ngkaring Village, Bungi District, Baubau City. The number of samples used in this study was 86 farmers who were divided into two categories, namely farmers who adopted and farmers who did not adopt. The sampling technique used the Cluster Random Sampling technique. The data collection technique in this study used observation, interview and documentation techniques. The data analysis method used in this study was logistic regression analysis. The results of this study indicate that the results of the logistic regression analysis show that the factors that influence farmers' decisions in adopting combine harvester technology innovations in Ngkaring-ngkaring Village, Bungi District, Baubau City are variables of land area, age, education, and farming experience have no significant effect on farmers' decisions in adopting combine harvester technology. While the variables that have a significant effect are land area and age and income have a significant effect but do not increase and do not decrease the level of farmers' decisions in adopting combine harvester technology.